Interactive Effects of Genotype and Molybdenum Supply on Yield and Overall Fruit Quality of Tomato - Sabatino, Leo; D'Anna, Fabio; Iapichino, Giovanni; Moncada, Alessandra; D'Anna, Eleonora; De Pasquale, Claudio (Frontiers in Plant Science, 2019)
Molybdenum (Mo) is an essential trace element for plant growth, development, and production. 18 However, there is little known about the function and effects of molybdenum in tomato plants. The 19 present study assessed the influences of different Mo concentrations on four tomato F1 hybrids 20 ('Bybal' F1, 'Tyty' F1, 'Paride' F1 and 'Ornela' F1) grown using a soilless system with different Mo 21 levels [0.0, 0.5 (standard NS), 2.0 and 4.0 μmol L-1, respectively]. The crop yield, plant vigour, fruit 22 skin colour, TA, fruit water content as well as the accumulation of SSC, and some antioxidant 23 compounds such as lycopene, polyphenols and ascorbic acid were evaluated. The minerals 24 concentration, including nitrogen (N), Mo, iron (Fe) and copper (Cu), were measured in tomato 25 fruits. Results revealed that tomato plants grown with 2.0 μmol Mo L-1 compared to plants grown 26 with 0.5 μmol Mo L-1 incurred a significant increase of total yield by 21.7%, marketable yield by 27 9.1%, aboveground biomass by 16.7%, plant height at 50 DAT by 6.5%, polyphenol content by 28 3.5%, ascorbic acid by 1.0%, SSC by 3.5%, N fruit content by 24.8%, Mo fruit content by 20.0% 29 and Fe fruit content by 60.5%. However, the Mo concentration did not significantly influence the 30 average fruit weight, b* fruit skin colour coordinate and TA. Furthermore, tomato fruits from plants 31 grown with 2.0 μmol Mo L-1 showed a lower Cu fruit content (16.1%) than fruits from plants grown 32 with 0.5 μmol Mo L-1 (standard NS). Consequently, our study highlights the different behavior of 33 the tomato genotypes tested when subjected to different levels of Mo concentration in the nutrient 34 solution. Nevertheless, taking all in consideration our results clearly suggest that a Mo fertilization 35 of 2.0 μmol Mo L-1 effectively enhance crop performance and overall fruit quality of tomato.